2012
DOI: 10.1186/1471-2369-13-173
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and the development of New onset chronic kidney disease over a 10 year period: a retrospective cohort study in a primary care setting in Malaysia

Abstract: BackgroundLittle is known about the rate of progression to chronic kidney disease (CKD) among hypertensive patients, particularly at the primary care level. This study aims to examine risk factors associated with new onset CKD among hypertensive patients attending a primary care clinic.MethodsThis is a 10-year retrospective cohort study of 460 patients with hypertension who were on treatment. Patient information was collected from patient records. CKD was defined as a glomerular filtration rate <60 ml/min per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
4
15
2
Order By: Relevance
“…This could have affected our renal function results among hypertensive donors. Reassuringly, as in previous studies , we found no evidence of further decline in renal function after 1 year, no proteinuria or albuminuria, and no donors at risk for end‐stage renal disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This could have affected our renal function results among hypertensive donors. Reassuringly, as in previous studies , we found no evidence of further decline in renal function after 1 year, no proteinuria or albuminuria, and no donors at risk for end‐stage renal disease.…”
Section: Discussionsupporting
confidence: 90%
“…Ageing and hypertension are reported to be associated with progressive decline in renal function in the general population . These factors are part of the extended eligibility criteria of live kidney donors indicating that they would even have an increased risk with just one kidney and no renal reserve left.…”
Section: Discussionmentioning
confidence: 99%
“…Glycemic control, hypoalbuminemia, and high mean blood pressure (BP) are several other risk factors for CKD in patients with diabetes mellitus (DM). Hypertensive patients who are older, with underlying DM, hyperuricemia, and lower baseline estimated glomerular filtration rate (eGFR) may be more likely to develop CKD …”
Section: Introductionmentioning
confidence: 99%
“…Hypertensive patients who are older, with underlying DM, hyperuricemia, and lower baseline estimated glomerular filtration rate (eGFR) may be more likely to develop CKD. 5 Visit-to-visit blood pressure variability (BPV) has been shown to be a determinant in contributing to cardiovascular morbidity and mortality. [6][7][8] Several studies have shown the relationship between visit-to-visit BPV and further decline of renal function in patients with established CKD.…”
mentioning
confidence: 99%
“…Clinical (e.g., age, smoking, diabetes, body mass index), biological (e.g., uric acid, HDL-cholesterol, triglycerides, homocysteine, C reactive protein, cytokines), and socioeconomic (e.g., education) factors associated with incident CKD and/or change in eGFR have been reported in prospective studies [7,8,9,10,11,12,13,14,15,16,17]. In addition to these factors, baseline kidney function (defined by eGFR or proteinuria) is independently associated with incident CKD and/or change in eGFR [18,19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%